Reinforcement of starch film with Castanea sativa shells polysaccharides: Optimized formulation and characterization - Amaral, Leonardo (2022)
Chestnut (Castanea sativa) shells, generated from the peeling process of the fruit, contains appreciable amounts of lignin and cellulose. In this work, a starch-based film reinforced with these polysaccharides was developed. Response Surface Methodology was employed to optimize the composition of the film with improved elongation, tensile strength, and elasticity modulus properties. The optimal film was characterized regarding structural, optical barrier and thermal properties. The optimum composition was obtained with 10% (w/w) fibers and 50% (w/w) glycerol; the elongation responses, tensile strength and modulus of elasticity reached values of 34.19%, 7.31 N and 4.15 N, respectively. The values of tension strength and modulus of elasticity were approximately 3.5 times higher than those obtained for the control film. The reinforced film was opaque and exhibited improved water solubility, UV-barrier capacity, and thermal stability compared to control. The optimized starch film based on chestnut shells fibers’ has the potential to produce biodegradable food packaging with improved properties.